1998
DOI: 10.1016/s0022-2275(20)33891-8
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous apoE expression modulates HDL3 binding to macrophages

Abstract: We have previously shown that expression of a human apoE cDNA in J774 macrophages enhances cholesterol efflux to HDL 3 . We have also shown that endogenous apoE expression produces a cell surface pool of apoE associated with proteoglycans. In this series of experiments, we first demonstrate the presence of a cell surface proteoglycan-associated apoE pool in human monocyte-derived macrophages. We then examine the hypothesis that endogenous expression of apoE modulates HDL 3 binding to macrophages, thereby, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In previously reported studies, we demonstrated the usefulness of the transfected J774 model to study the effect of apoE expression on cholesterol flux in macrophages (21,23,24). We showed that cholesterol efflux produced in this model is very similar to that observed in human monocyte macrophages, in terms of amount of cholesterol and phospholipid secreted, the density of the apoEcontaining lipid particle, and the response of cholesterol and phospholipid efflux to enriching cells with excess cholesterol.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…In previously reported studies, we demonstrated the usefulness of the transfected J774 model to study the effect of apoE expression on cholesterol flux in macrophages (21,23,24). We showed that cholesterol efflux produced in this model is very similar to that observed in human monocyte macrophages, in terms of amount of cholesterol and phospholipid secreted, the density of the apoEcontaining lipid particle, and the response of cholesterol and phospholipid efflux to enriching cells with excess cholesterol.…”
supporting
confidence: 59%
“…Proteoglycans provide important binding sites for growth factors and cytokines, and the presence of apoE could potentially modulate retention of these factors on the macrophage cell surface. We previously showed that apoE on the macrophage cell surface modulates the interaction of cells with HDL (24). It was also recently shown that apoE in a pericellular proteoglycan matrix modulates the metabolism of apoE-containing triglyceride-rich lipoproteins by macrophages (40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All tissue culture reagents were obtained from Gibco (Grand Island, NY). All other materials were from previously described sources (8)(9)(10)(11)(12)14).…”
Section: Methodsmentioning
confidence: 99%
“…Whether apoE has an intracellular function, or exists in a discrete intracellular pool separate from the secretory pathway, is not yet completely clear. However, there does appear to be a distinct cell surface pool of macrophage apoE which has been identified in human monocyte-derived macrophages and in J774 cells transfected to express human apoE (10,14,15). Involvement of cell surface proteoglycans in the formation of the macrophage cell surface pool of apoE has been clearly established (10,14,15).…”
mentioning
confidence: 99%